Coastal resources management: Ulugan Bay, Palawan Island, the Philippines - Fazi, S. and P. Flewweling (eds.) (Jakarta, Indonesia, 2001)
Contents: vol.1 Ecology, culture and socio-economics.vol.2 Master plan for community based eco-tourismvol.3 An integrated management model.